Strong thermostable interference coatings for IR optical elements - Zagoruiko, Yu.A.; Fedorenko, O.A.; Kovalenko, N.O.; Mateychenko, P.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Interference ZnO coatings for IR optical elements are obtained by the method of photothermal oxidation on the surface of crystalline ZnSe. Investigated are their mechanical and optical properties. The obtained oxide coatings possess high adhesion, homogeneity, withstand repeated thermocycling and irradiation with high-intensity CO₂-laser radiation. Revealed is the formation of islets of oxide films with elevated mechanical strength.